ORGANIZATIONAL SUPPORT AND CUSTOMER SERVICE EFFICIENCY IN THE HOSPITALITY SECTOR IN NIGERIA - Samuel Adedoyin; Ernest Amiens; Airenvbahihe Igbinedion; Samson Abolarinwa (ZILLZELL MEDIA PRIMA, 2025)
This study investigated the influence of perceived organizational support - specifically employer, supervisor, and coworker support - on customer service efficiency within hospitality organizations in Nigeria. Using cross sectional research design and with data elicited from a sample of 252 respondents, the study employed descriptive and inferential analyses to evaluate the relationship between various support dimensions and service delivery outcomes. The results reveal that all three forms of organizational support contribute positively to customer service efficiency, with supervisor and coworker support emerging as particularly strong predictors. While employer support was slightly lower in perception, its role remains critical in shaping employee engagement and service behavior. These findings highlight the need for organizations to adopt a holistic support strategy that integrates formal institutional backing with interpersonal dynamics. The study underscores the importance of nurturing a supportive work environment to enhance customer-facing performance and recommends further exploration of contextual factors that may moderate these relationships.